α-Glucosidase Inhibitory Activities of Isoflavanones, Isoflavones, and Pterocarpans from Mucuna pruriens - Dendup, Tshewang; Prachyawarakorn, Vilailak; Pansanit, Acharavadee; Mahidol, Chulabhorn; Ruchirawat, Somsak; Kittakoop, Prasat (Planta Medica, 2014)
Three new isoflavanones (1–3) and thirteen known compounds (4–16) were isolated from the roots of Mucuna pruriens. The absolute configurations of isoflavanones 1–3 and parvisoflavanone (4), lespedeol C (5), and uncinanone C (6) were addressed by a circular dichroism technique. Isoflavanones, isoflavones, and pterocarpans of M. pruriens were found to be α-glucosidase inhibitors. Medicarpin (7) and parvisoflavone B (9) were potent α-glucosidase inhibitors (twofold less active than the standard drug acarbose). The production of bioactive metabolites in M. pruriens seems to be season-dependent.
Keywords: Mucuna pruriens; Fabaceae; α-glucosidase inhibitor; isoflavanone; isoflavone; pterocarpan